In Vitro Induction of Neospora caninum Bradyzoites in Vero Cells Reveals Differential Antigen Expression, Localization, and Host-Cell Recognition of Tachyzoites and Bradyzoites - Vonlaufen, Nathalie (American Society for Microbiology, 2004)
We report on an optimized method for the in vitro culture of tissue cyst-forming Neospora caninum bradyzoites in Vero cells and the separation of viable parasites from host cells. Treatment of tachyzoite-infected Vero cell cultures with 17 μM sodium nitroprusside for 8 days severely scaled down parasite proliferation, led to reduced expression of tachyzoite surface antigens, and induced the expression of the bradyzoite marker NcBAG1 and the cyst wall antigen recognized by the monoclonal antibody MAbCC2. Transmission electron microscopy demonstrated that intracellular parasites were located within parasitophorous vacuoles that were surrounded by a cyst wall-like structure, and the dense granule antigens NcGRA1, NcGRA2, and NcGRA7 were incorporated into the cyst wall. Adhesion-invasion assays employing purified tachyzoites and bradyzoites showed that tachyzoites adhered to, and invaded, Vero cells with higher efficiency than bradyzoites. However, removal of terminal sialic acid residues from either the host cell or the parasite surface increased the invasion of Vero cells by bradyzoites, but not tachyzoites.